PERUBAHAN NILAI-NILAI ADAT NYABANGK PADA ETNIS DAYAK BAKATI DI DESA SANGO KECAMATAN SANGGAU LEDO - Dita, Dita; Bahari, Yohanes; Hidayah, Riama Al (Universitas Tanjungpura, 2022)
AbstractThis study aims to determine changes in the value of human relations with God, changes in the value of human relations with other people or with each other and changes in the value of human relations with nature in the nyabangk tradition in Sango Village, Sanggau Ledo District. Descriptive qualitative research method. The sources of data in this study were people who played an important role and participated in the ritual activities of the nyabangk traditional ceremony, namely the traditional elders, community leaders, the head of the RT and the village head. Primary data sources and secondary data sources are the data sources used in this study. Data collection techniques and tools are by observation, interviews and documentation. Data analysis techniques through four stages, namely analyzing data, reducing data, presenting data and drawing conclusions. The results of this study indicate that the value of the relationship between humans and God, namely believing in God contained in religious values, these values have undergone changes caused by the influence of religion and belief in the existence of the supernatural contained in values that have undergone changes by religious and developmental factors. era. The value of human relations with other people, namely deliberation which is contained in democratic values, has undergone changes caused by the times and the value of mutual cooperation contained in the value of togetherness, these values have undergone changes caused by factors of the times, economy, the existence of a religion that contrary to the nyabangk custom. The value of human relations with nature, namely nature provides needs for humans and humans utilize nature in it which is contained in the value of use, this value has undergone changes caused by factors of the times, human nature is greedy, selfish, worldly interests, and the nature contained therein, responsibility, these values have changed due to the lack of public awareness of responsibility, the times, human nature is greedy, selfish, and worldly interests.Keywords: Changes in Values, Nyabangk Custom, Ethnic Dayak Bakati.